PEMBERDAYAAN KEMITRAAN MASYARAKAT MELALUI PENGEMBANGAN EKOSISTEM PENGELOLAAN SAMPAH TERPADU TPS 3R GUNA MENDORONG PEMBANGUNAN BERKELANJUTAN - Nurussa'adah, Erfina; Astari, Devi Wening; Amrullah, Yusuf Amri (Jurnal Abdi Insani, 2024)
Solid waste in the form of garbage is one of the problems that occurs in various big cities in Indonesia. TPS 3R Migunani Plalangan, Pandowoharjo Sleman Yogyakarta, using the need and assessment method, found problems that cover two aspects, namely production and marketing. Through the development of an integrated waste management ecosystem for TPS 3R Migunani, it is hoped that it can support the 2020-2024 National Medium-Term Development Plan (RPJMN) with a priority on waste management, namely through waste processing by implementing Reduce, Reuse, and Recycle by optimizing production and increasing the selling value of TPS 3R Migunani commodities, namely compost, maggots, bricks and superior Balitbangtan chickens to encourage sustainable development. The stages in implementing the method are procuring goods to sort/enrich waste. Furthermore, for the aspect of improving marketing by creating product packaging designs and also making digital marketing videos to reach a wide market so that waste management can run effectively, efficiently and sustainably. The empowerment program by providing assistance in waste management at TPS 3R Migunani, Plalangan has succeeded in helping develop a waste management ecosystem by increasing the economic value of waste and reducing waste residue disposed of at the TPA. It has also succeeded in increasing the volume of waste processing production which has boosted the production of fresh maggots and compost. The advice from the devotee for the sustainability of a sustainable waste management ecosystem in order to realize a circular economy in the Plalangan Village environment is to strengthen collaboration with various stakeholders, each of whom plays a role in waste management. Not just relying on social network approaches. Thus, slowly but surely it will be able to realize zero waste in the Plalangan Village environment and its surroundings.